Synadenium umbellatum: cytotoxicity and DNA damage to bone marrow cells from mice (Revista Brasileira de Ciências Farmacêuticas, 2007)
In the present study we investigated, in vitro and in vivo, the cytotoxic and mutagenic potential of the Synadenium umbellatum ethanolic extract (SUEE) on the bone marrow cells of mice. In vitro cytotoxicity was assayed incubating bone marrow cells with different concentrations (40-0.312 mg/mL) of SUEE for 12, 24 or 48 h using the MTT tetrazolium reduction test and the trypan blue exclusion test. The micronuclei assay was performed to determine mutagenic effects of mice orally exposed to different doses of SUEE (10, 25 or 50 mg/kg/day) in 24 h. Our results demonstrated that SUEE has, in a dose-dependent manner, potential cytotoxic and mutagenic effects on the bone marrow cells of mice. Further studies are needed to expand the knowledge of the toxicological/pharmacological potential of the SUEE.